Exploring the contribution of dietary protein from poultry by-product meal and fish meal to the growth of catfish Ictalurus punctatus by means of nitrogen stable isotopes - García Pérez, Oscar Daniel; Cruz Valdez, Julio César; Ramírez Martínez, Carlos; Villarreal Cavazos, David Alonso; Gamboa Delgado, Julián (2018)
The natural nitrogen stable isotope signatures (δ 15N) found in poultry by-product meal (PBM) and fish meal (FM) were used to estimate the relative contribution of dietary nitrogen supplied by both ingredients to the somatic growth of juvenile channel catfish Ictalurus punctatus. Six isonitrogenous and isoenergetic experimental diets were formulated using FM and PBM. Two of these diets consisted of isotopic controls having only one ingredient supplying dietary nitrogen, either FM or PBM. Four combined diets were formulated with varying proportions of these ingredients in order to supply high proportions of PBM (FM:PBM, 50:50, 35:65 20:80 and 5:95) on a nitrogen basis. There were significant differences in mean final weight of fish at the end of the trial. Lower growth was observed as the dietary level of PBM increased. In order to determine the relative contributions of the dietary nitrogen supplied by FM and PBM to catfish growth, an isotopic mixing model was applied. Results indicated that the incorporation of dietary nitrogen supplied by PBM was equivalent to the die tary proportions. The dietary nitrogen available in combined diets containing 50, 65 and 80% of PBM was incorporated in fish bodies as 50, 62 and 81%, respectively. However, high incorporation of dietary nitrogen from PBM was not always reflected in higher growth rates. Results demonstrate the viable use of stable isotopes to determine the allocation of dietary nitrogen and indicate that practical diets for catfish can be formulated with levels of PBM as high as 65% without affecting growth and survival.